A review of prefab home and relevant issues. - Abang Ali, Abang Abdullah; Panjehpour, Mohammad (2013)
Having an easily built house has been always one of human wishes. Prefabricated home makes this wish come true because of its affordability and fast completion. This paper gives an overview of different types of prefab home and its terminology. This review sheds light on the characterisation of prefab home, which takes the aspects of off-site technology, mass customisation, and sustainability into consideration. This paper is confined to general review of prefab home without going through different systems utilised in off-site technology. In spite of the fact that prefab home has many advantages, which are discussed in this review, it suffers from a few drawbacks which should be considered by designers. Various exploitations in this field may merit further research in future, including finding the optimum prefabricated systems among the existing systems such as roof, wall, and floor systems for different applications of prefab homes. Nevertheless, there is still a universal design and practice code for prefab homes that emphasize on green technology and sustainability yet to be discovered.